Novel phenoxazine-benzonitrile and phenothiazine-benzonitrile donor-acceptor molecules with thermally activated delayed fluorescence (TADF). (April 2020) - Baraket, Faiza; Pedras, Bruno; Torres, Érica; Brites, Maria João; Dammak, Mohamed; Berberan-Santos, Mário N.
Abstract: Four novel TADF emitters, containing phenothiazine and phenoxazine as electron-donors and benzonitrile derivatives as electron-acceptors were synthesized and fully characterized. Their photophysical (absorption and emission spectra, molar extinction coefficients, fluorescence quantum yields and lifetimes) and electrochemical properties (HOMO and LUMO energy levels) were measured, and drop-cast solid films of the four compounds were obtained to perform TADF studies. The obtained values for ΔEST indicate that these compounds are candidates for OLED applications. Highlights: Four new donor-acceptor (DA) molecules of the phenothiazine-benzonitrile and phenoxazine-benzonitrile types. All DA molecules display thermally activated delayed fluorescence. All DA molecules have a small singlet-triplet energy gap.